2012
DOI: 10.1016/j.ejca.2011.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Sham-controlled, randomised, feasibility trial of acupuncture for prevention of radiation-induced xerostomia among patients with nasopharyngeal carcinoma

Abstract: Background Xerostomia (dry mouth) after head/neck radiation is a common problem among cancer patients. Quality of life (QOL) is impaired, and available treatments are of little benefit. This trial determined the feasibility of conducting a sham-controlled trial of acupuncture and whether acupuncture could prevent xerostomia among head/neck patients undergoing radiotherapy. Methods A sham controlled, feasibility trial was conducted at Fudan University Shanghai Cancer Center, Shanghai, China among patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 32 publications
2
85
0
Order By: Relevance
“…Over the past decade, there has been a dramatic increase in the use of complementary and alternative medicines by cancer patients despite limited research available to support their use [6]. In this regard, acupuncture has been used to treat the side effects of cancer therapy as well as the fatigue, pain, sleep disturbances, and lymphedema associated with many types of tumors [13, 32, 33]. While there are a number of studies that have provided evidence for the antinociceptive, antifatigue, and antiemetic effects of EA in cancer patients [4, 33], there is only one case report that suggests that acupuncture may actually affect the tumor itself (by causing regression of human ductal carcinoma [34]).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been a dramatic increase in the use of complementary and alternative medicines by cancer patients despite limited research available to support their use [6]. In this regard, acupuncture has been used to treat the side effects of cancer therapy as well as the fatigue, pain, sleep disturbances, and lymphedema associated with many types of tumors [13, 32, 33]. While there are a number of studies that have provided evidence for the antinociceptive, antifatigue, and antiemetic effects of EA in cancer patients [4, 33], there is only one case report that suggests that acupuncture may actually affect the tumor itself (by causing regression of human ductal carcinoma [34]).…”
Section: Discussionmentioning
confidence: 99%
“…The Shanghai Group from Fudan University published 2 trials 26, 27. First was a feasibility study followed by a prospective randomized trial, both with the target symptom xerostomia.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is observed in the verum acupuncture and in the sham acupuncture arms at least in 3 trials. The group of Meng and coworkers demonstrated a significant benefit of verum acupuncture compared with sham acupuncture 26, 27. One trial is still ongoing 28 ; thus, controversial data exist and further clarification is required.…”
Section: Discussion and Future Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…44 EA preconditioning, S100 calcium-binding protein beta & neuron-specific enolas 45 Sevoflurane anesthetic requirement, and the speed of postoperation recovery 46 Head-and-neck cancer Transcutaneous nerve stimulation method, whole saliva production & related symptoms with radiation-induced xerostomia 47 Xerostomia among head/neck patients undergoing radiotherapy [48][49][50][51] Swallowing function and QoL in patients with dysphagia 69 resulting in a number of research studies on the effectiveness and safety of acupuncture. Taking into account the study period, this trend has been confirmed in acupuncture for cancer-related diseases, and, since 1979, the article numbers have been increasing gradually (Fig.…”
mentioning
confidence: 99%